Impacto del programa juntos en las necesidades básicas insatisfechas, pobreza, salud y educación en los beneficiarios de la región Junín - Fabian-Arias, Eugenia (2021)
The Juntos Program is a conditional cash transfer program that grants a bimonthly S / 200 soles bonus to households living in poverty and extreme poverty. The objective of the study was to know the impact of the Juntos Program on unsatisfied basic needs, poverty, health and education in the Junín Region, type of basic research, descriptive level, quantitative character, quasi-experimental design, the analysis units were the beneficiaries schedule together. The population was 3,990 households and the treatment sample was 1,459 households and 1,399 households for the control group from 2014 to 2019; the research method was Differences in Differences with data from the National Household, Demographic and Family Health Surveys and processed with the Stata 15 software. The results in unsatisfied basic needs generated a significant low-level impact on the type of housing and lighting by electric generator; in poverty there was evidence of a moderately significant impact; but no significant results were found in the health indicators; in education the enrollment of children and adolescents generated a moderately significant impact; In the mother tongue or tongue, a positive impact of a low significant level was evidenced and regarding the monthly tuition pension, a negative impact of a moderately significant level of the program was observed. It is concluded that some indicators of low significant level were found in unsatisfied basic needs, poverty and education and no significant results were found in health.